(untitled) (Research, Society and Development, 2020)
To investigate the perception of undergraduate nursing students about the teaching career of higher education at a public university in southern Brazil. This is a qualitative, exploratory-descriptive study consisting of twenty-seven nursing students, enrolled between the first and ninth grades of the course. Data collection took place between May and June 2017, semi-structured interviews were used. The data were analyzed according to the textual discursive analysis. Based on the results obtained, from the data analysis, three categories emerged: Students’ perception of the entry and exercise of the teaching career; Teacher’s role / duties; and Challenges for exercising the profession with quality. The conclusions indicated that teachers should be aware of the perceptions of nursing students about the teaching career, so that these professionals are able to better meet the needs and expectations of their students, contributing to the strengthening and quality of teaching and learning.